Relationship Between A Premature Rupture Of Membranes And The Increase Of Leucocyte Levels In Pregnant Women During COVID-19 Pandemic - Rinieta Sausan Margono; Adi Sukrisno; Nunuk Nugrohowati; Winda Lestari (Poltekkes Kemenkes Surakarta, 2021)
Background: Premature Rupture of Membranes (PROM) is a condition in which the membranes rupture before women’s delivery. The incidence of PROM in Indonesia is still quite high, around 4.5%-7.6% from all pregnancies. The incidence rate at DKI Jakarta in 2020 was 4.6% while at Pelni Hospital in the same year was 7.9%. The main cause of this incident was due to the occurrence of infection that spreads into the uterus and amniotic fluid as well as due to the inflammatory process. This causes arachidonic acid metabolism to be active so that the level of leucocytes in the blood being increase. The purpose of this study was to analyze the relationship between the incidence of PROM and leucocyte increasing levels at the Pelni Hospital during the COVID-19 pandemic in 2020. Methods: The study had used analytic observational method with cross sectional approach. The number of samples were 97 people, done by simple random sampling technique, using Medical Records of respondents along year of 2020. Results: Data showed the aged range of respondents were 20-35 years (79.4%); multigravida (53,6%); PROM (76.3%); respondents with method of delivery which done by cesarean section (71.1%); and respondents with PROM who experienced the increasing of leucocyte levels (80.4%). Results based on Chi-square test showed there was a relationship between PROM and increased leucocyte levels (p=0.036). Conclusion: The relationship between PROM and the increasing of leucocyte levels to pregnant women at Pelni Hospital during COVID-19 pandemic in 2020 possibly caused by the presence of infections from ascending microorganisms.